Impact of Store Size on Impulse Purchasing Behaviour of Respondents: A Study with Reference to Coimbatore, Tamil Nadu - Palaniswamy, R.; Dinesh Kumar, S.; Selvakumar, N. (Indian Journal of Marketing, 2012)
An impulse purchase or impulse buy is an unplanned or otherwise spontaneous purchase. Impulse buying disrupts the normal decision making models in consumers' brains. The logical sequence of the consumers' actions is replaced with an irrational moment of self-gratification. Impulse items appeal to the emotional side of consumers. Marketers and retailers tend to exploit these impulses which are tied to the basic want for instant gratification. Several researchers have studied impulse purchase with respect to customers' behavior and also how the size of a mall influences the impulse purchase behavior. In the present study, the researchers are made an attempt to find out the impact of store size on impulse purchasing behaviour in Coimbatore, Tamil Nadu.